(untitled) (American Journal of Education and Technology, 2024)
This study aimed to explore the lived experiences of struggling readers in junior high school. This study was limited to four (4) participants who were under frustration reading level and had repeated grade 7. It was very particular with the lived experiences of the participants which resulted in their difficulties. Giorgi’s descriptive phenomenological study was the basis of this study. In light of the findings, the following conclusions were drawn. Participants in this study experienced difficulties such as emotional, academic, and behavioral problems. However, through this phenomenon, the participants were able to cope by emotion-focused mechanisms which were considered as poor coping mechanisms wherein the participants opted to exert effort to regulate the emotional consequences of stressful or potentially stressful events. One coping strategy that emerged was Physical Distancing wherein participants distance themselves from the things or people that give them stress or move away from a threat. Another coping mechanism exemplified by the participants was the Emotional Distancing strategy wherein struggling readers move away emotionally. It was likely that experiences, themes, techniques, and strategies described by students in this population would give teachers a new outlook from which they can enhance learning outcomes. The following recommendations were laid down: the use of a holistic approach in reading intervention since struggling readers experience difficulties in different aspects of life such as emotional, academic, and behavioral aspects; conducting a phenomenological study on the life of elementary struggling readers is also recommended since there is a much bigger number of struggling elementary readers in some regions in the country.